GROUP TESTING - Zahidah, Siti
Historically, group testing theory related to the testing of blood samples to identify a disease. Based on the algorithm, there are two types of group testing, Adaptive Group Testing (AGT) and Non-Adaptive Group Testing (NAGT). NAGT algorithm can be represented by a binary matrix M = (mij), where coloumns are labeled by items and rows by tests (blocks). Criteria matrix is mij = 1 if test i contains item j and the other mij = 0. On the other hand, the test results of each block is repre- sented in a column vector, called outcome vector. Based on these representations, the problem of group testing can be viewed as nding representation matrix M which satises the equation Mx = y where y is an outcome vector and x samples are tested. If there are d positive sample of n samples then we say d-Combinatorial Group Testing, abbreviated by d-CGT. In this thesis will show the construction of d-disjunct matrices which is a solution of group testing equation. Furthermore, from the construction will be modied so that the new construction can be identied more than d positive samples.